Pengaruh Sponsorship Pada Event Bingen Fest Terhadap Brand Awareness Authenticity Clas Mild - Pelliyezer Karo Karo; Annis Sabilla Firstyana (LONTAR: Jurnal Ilmu Komunikasi, 2021)
Corporate investment in the form of sponsorship is often carried out to establish and maintain information stability in consumers, which leads to brand awareness of products and companies. The amount of the sponsorship budget is often not on target so that its effectiveness cannot be measured. In this regard, by taking the case of the Bingen Fest event in Palembang, the research was conducted aimed at identifying how far the influence of sponsorship by Clas Mild on the development of Brand Awareness Authenticity, so that it can be used as a basis for consideration of sponsorship financing in the future. The research sample consisted of 213 respondents who were visitors to the event and the research analysis used was simple linear regression. The test results show that 90.6 percent of the event segment is generation Z with a visit repetition rate of 64.88 percent. Clas Mild sponsorship itself has a strong impact with a large influence of 49.1 percent on the development of Brand Awareness Authenticity.